2008
DOI: 10.1021/ic701657r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bismuth-Thiolate-Carboxylate Clusters by Electrospray Ionization Mass Spectrometry

Abstract: The known thermal and hydrolytic stability of bismuth-sulfur bonds indicates that biological targets for bismuth likely involve thiol or thiolate functionalities, such as in L-cysteine. Complexes of bismuth with cysteine or other thiol-carboxylic acid ligands have been isolated and characterized providing a preliminary view of the potential participation of these functional groups in the biochemical mechanisms involving bismuth. A broader assessment of bismuth-thiolate interactions has been possible using elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…4d and e), implying that the lone pair electrons contribute to the stereochemistry of the Bi 3+ binding. Our results are consistent with the report by Phillip and Burford who showed that Bi 3+ compounds with small coordination number are stereochemically active [53]. However, for (3), the ligand O on the axial position in Fig.…”
Section: Molecular Geometrysupporting
confidence: 93%
“…4d and e), implying that the lone pair electrons contribute to the stereochemistry of the Bi 3+ binding. Our results are consistent with the report by Phillip and Burford who showed that Bi 3+ compounds with small coordination number are stereochemically active [53]. However, for (3), the ligand O on the axial position in Fig.…”
Section: Molecular Geometrysupporting
confidence: 93%
“…In attempts to rectify this deficiency, main group chemists have investigated bismuth coordination complexes with ligands that 166 T. CHIVERS AND J. KONU contain biologically relevant functionalities, e.g., thiol, amino and carboxyl groups. [142] The very low solubility of bismuth complexes presents a major challenge for solution studies and for the production of single crystals for X-ray diffraction studies. However, electrospray ionization mass spectrometry has been used effectively to determine the molecular compositions of such complexes.…”
Section: Medicinal Chemistrymentioning
confidence: 99%
“…However, electrospray ionization mass spectrometry has been used effectively to determine the molecular compositions of such complexes. [142] Carboranes have been widely studied for their medicinal applications. [143] Early work focused on the use of carboranes in boron neutron capture therapy (BNCT); the isotope 10 B (abundance ca.…”
Section: Medicinal Chemistrymentioning
confidence: 99%
“…We reported the first structures of Bi(Hsal) 3 as adducts of 2,2 0 -bipyridine and 2,2 0 -phenanthroline in 2002 [14] and related derivatives of [PhBi(Hsal) 2 ] and [PhBi(4-Me-2-OH-C 6 H 3 CO 2 ) 2 ] followed shortly thereafter [15]. Andrews [23]. In order to increase our understanding of the parameters affecting the solvolysis and hydrolysis of the bismuth carboxylates in general, we have extended our synthetic work to producing complexes derived from salicylic and anthranilic acids containing electron-donating and electron-withdrawing substituents (Fig.…”
Section: Introductionmentioning
confidence: 98%